HEALTHY LIFESTYLE, ROLE STRESSOR DAN GAYA KEPEMIMPINAN: STUDI EMPIRIS KINERJA AUDITOR PEMERINTAH - Luh Komang Merawati; Ni Putu Intan Dewi Prayati (Universitas Pendidikan Nasional, 2017)
The level of public confidence was greatly affects by the performance of an auditor as a benchmark of the work in conducting the audit process. This research was conducted to know the influence of healthy lifestyle, role stressor and leadership style on auditors performance. Data were collected through questionnaires distributed to 120 auditors working in BPKP office and BPK Representative of Bali Province. Instrument testing is done through validity and reliability test and data was analyzed with multiple linear regression analysis. The research result shows that the variables of healthy lifestyle, role ambiguity and role overload does not affect the performance of auditors, while the variable role conflict has a negative effect on the auditors performance and leadership style has a positive effect on the performance of auditors in the office of BPKP and BPK Bali Province RepresentativeKeyword: healthy lifestyle, role stressor, leadership style, auditors performance